Pengaruh Keterlibatan Pemakai Sistem, Program Pelatihan dan Pendidikan, Kemampuan Teknik Personal, Dukungan Manajemen Puncak, dan Formalisasi Pengembangan Sistem Informasi Terhadap Kinerja Sistem Informasi Akuntansi di Bank Umum Kota Surakarta - Hutama, Raka Cakra; , Dra. Rina Trisnawati, Ak, M.Si, Ph.D (2017)
This study purposes to analyze the influence of the system user involvement in the development of AIS, training and education programs, personal technical ability IS, top management support, and the formalization of the development of the SIA on the performance of accounting information systems at commercial banks in Surakarta. The population in this study is employees of a commercial bank in Surakarta. The method to determine sample used purposive sampling, the sample are 36 respondents, 14 respondents employees of Bank Danamon and 22 respondents employees of Bank BTN. Data were analyzed using linear regression with SPSS software version 21.00. These results suggest the involvement of users of the system variables in the development of AIS, training and education programs, technical skills and personal SI AIS formalization development significantly affect the performance of the accounting information system. Top management support variables did not significantly affect the performance of the accounting information system.